Professional women balancing work and motherhood : a study of coping strategies used in balancing this dual role - Gunton, Andrea (Rhodes University, Faculty of Humanities, Department of Psychology, 2012)
The aim of this qualitative research study is to develop insights into the dynamics involved in work- family conflict, balance and coping strategies. The study explores the experiences of seven professional women, who are also mothers, employed in professional work positions in Grahamstown. The research is interpretive in nature as it aims to explore the conflicts experienced by the professional mothers in balancing their competing roles. The study focused on the demands that these women face and the coping strategies that these working mothers develop and use, in order to balance their career aspirations as well as their family responsibilities. It set out to explore the women's perceptions of work- family conflict and the extent to which they experience it, further examining the compromises that the women have had to make and possible feelings of guilt or regret that they may have experienced. The findings indicated that this balance is sensitive to many facilitating and hindering factors. The participants revealed that they experience work- family conflict, and that the experience of it has largely to do with the guilt of not spending enough time with their family. Another significant finding was that the women expressed their coping strategies as being organised; forming a line between work and family life as well as employing domestic workers. The women further stated that there are constant compromises that have to be made to fit in the multiple roles, and that feelings of guilt and/or regret do set in at times.
Keywords: Working mothers -- South Africa -- Grahamstown; Work and family -- South Africa -- Grahamstown; Role conflict; Stress (Psychology); Working mothers -- Psychology